The henchman's war - Greene, Anthony M.; Kain, Rick; Leembruggen, Robert; Petkofsky, Jane E.; Skyrocket Productions; Leomark Studios (Firm) ([Waco, Tex.] : Skyrocket Productions, LLC, 2012)
On assignment to kill a failed candidate, mob henchman Joe King also kills his wife, Miranda, a key component to why he lives a life of crime in obedient silence. Encompassed with regret and rage, Joe sets about killing those he blames for the traumatic events he and Miranda have endured. --
A deadly mistake sets an introspective henchman on a violent crusade against a mid-level crime boss with demons of his own.
Originally released as a motion picture in 2012
Rick Kain, Robert Leembruggen, Jane E Petkofsky, Paul Sieber, Tamieka Chavis, Alexander Yi, James J. Johnson, Andrea Baker.
Cinematographer, K. Quin Paek ; editors, JD Medlock, Becky Varni ; music, Beau Finley.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 8, 2018)
Keywords: Crime films; Action and adventure films; Feature films; Internet videos; Streaming video